Pilgrimage to Brahmananda Keshab Chandra Sen - Das, Matilal, Inspector of schools (Matilal Das ; To be had of Navabidhan Publication Committee, 1938)
On the activities of Keshub Chunder Sen, 1838-1884, founder of the Brahma-samaj and its doctrines.